Representação e persistência para acesso a Recursos Informacionais Digitais gerados dinamicamente em sítios oficiais do Governo Federal - Modesto, Lisandro Rogério [UNESP] (2013)
The Access to Information Act, enacted on November 18, 2011 by the Acting President of the Republic Dilma Rousseff, repealed the law number 11.111/1995 from May 16, 2012. This law regulates the constitutional right of access to public information by Brazilian citizens, being applied to 3 powers of the Federal Government, State Government and Local Government. With this law, the official government sites were forced to leave information available on their portals. Although this law imposes an availability of information of public interest, it does not define how such information should be made available. Even with the Law on Access to Information, the official websites do not provide the information so that citizens can understand it. To resolve this situation, the ideal would be that the information be made available in an open format, allowing analysis and use. This work is restricted to official sites of the Federal Government can extrapolate other contexts, which should make information available given the governing Law on Access to Information. How the information is provided is not currently possible to access research results with data dynamically generated from input or selected on the official sites of the Federal Government parameters again. From the persistence / materialization of the results and dynamically aggregates generated metadata can ensure the reuse of information from official websites of the Federal Government. The objective of this work is to propose a model of representation of Digital Informational Resources dynamically generated, provided by the Federal Government on their official websites, using metadata to describe and access resources such persists to enable reuse and secure new forms of recovery. To allow the persistence of Digital Informational Resources dynamically generated was developed MDDIR Tool to describe access to Digital Resources Informational dynamically...